High-density printed circuit board interconnection copper paste, preparation method and application thereof

By using copper slurry coated with nano copper powder and corrosion inhibitor in high-density printed circuit board interconnection, combined with low-temperature surface drying and high-temperature high-pressure processes, the problem of copper interface oxide layer and pressure uniformity is solved, and high density is achieved. Reliable porous interconnects improve thermal conductivity and productivity.

CN119252529APending Publication Date: 2025-01-03SHENZHEN BAROY NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411673947.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the interlayer interconnection between high-density porous printed circuit boards, the copper interface oxide layer exists and the pressure uniformity is poor, resulting in poor reliability and thermal conductivity, and the low yield of low-temperature nanosintering technology.

Method used

Using a high-density printed circuit board interconnection copper slurry, containing micron copper powder, coated nano copper powder, organic solvent, corrosion inhibitor and thickener, nano copper powder is used under pressure or uneven pressure conditions. The pre-melting and corrosion inhibitor removes the oxide layer, combining low-temperature surface drying and high-temperature high-pressure pressing processes to achieve high-density interconnection.

Benefits of technology

It realizes premelting and oxide layer removal of high-active nanometal powder at high temperatures above 180 degrees at normal pressure, retains the conductive thermal performance, reduces the pressure uniformity requirements, and improves the compressed yield and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252529A_ABST
    Figure CN119252529A_ABST
Patent Text Reader

Abstract

The invention discloses high-density printed circuit board interconnection copper paste, a preparation method and an interconnection process, the interconnection copper paste comprises the following components in parts by weight: 30-90 parts of micron copper powder, 10-80 parts of nano copper powder, 4-10 parts of an organic solvent, 0.01-2 parts of a thickening agent and 0.5-3 parts of a corrosion inhibitor, and the nano copper powder is nano copper powder coated by an organic coating agent. According to the interconnection copper paste, the specially treated nano copper powder is applied, the high-activity nano copper powder is pre-melted at the high temperature of 180 DEG C or above under the normal pressure, meanwhile, the corrosion inhibitor introduced into the formula effectively removes an oxide layer in the baking process, good bonding with a copper bonding pad is achieved, and the high pressing yield can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pressureless sintering conductive paste, and in particular relates to a high-density printed circuit board interconnection copper paste, a preparation method and application thereof. Background Art

[0002] Multilayer printed circuit boards (PCBs) achieve circuit conduction between layers, usually using through-hole copper deposition and electroplating copper to electroplate a metal layer on the through-hole wall to achieve metallization of the through-hole wall to form a conductive circuit. Since this process produces chemical waste liquid and is inefficient, the industry has proposed transient liquid phase diffusion connection (TLP) and low-temperature nano-sintering interconnection technology, using screen printing to plug holes, and forming metal pillars after pressure sintering to achieve conductive interconnection between upper and lower layers. Among them, the intermetallic compounds formed by TLP technology are brittle and have low thermal conductivity (not more than 70W / mK). The low-melting-point alloys contained are prone to secondary melting and creep, and have poor reliability. The upper and lower layers of PCBs are generally interconnected by copper and copper, and there is inevitably an oxide layer on the surface of the substrate. Since low-temperature nano-sintering relies on diffusion between metal atoms, the presence of the oxide layer seriously affects the bonding force. In response to the high-density porous interconnection direction, due to the large number of holes and high density, it is difficult to ensure consistency in single-hole pressure and interface oxidation degree, resulting in a lack of guarantee of production yield.

[0003] Therefore, it is particularly important to develop a pressureless sintering slurry for high-density porous PCB interlayer interconnection that has reducing properties to the copper interface oxide layer, low pressure uniformity requirements, high reliability, and excellent electrical and thermal conductivity. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a high-density printed circuit board interconnection copper paste, creating a bonding technology with excellent contact strength under conditions of no pressure or uneven pressure, solving the problems of poor reliability of TLP interconnection technology and low yield of nano pressure sintering interconnection technology in high-density porous PCB interconnection.

[0005] Another object of the present invention is to provide a method for preparing the interconnect copper paste.

[0006] Another object of the present invention is to provide the application and packaging process of the interconnect copper paste.

[0007] In order to achieve the above invention object, the present invention adopts the following technical solution:

[0008] A high-density printed circuit board interconnection copper paste comprises the following components in parts by weight: 30-90 parts of micron copper powder, 10-80 parts of nano copper powder, 4-10 parts of organic solvent, 0.01-2 parts of thickener, and 0.5-3 parts of corrosion inhibitor, wherein the nano copper powder is nano copper powder coated with an organic coating agent on its surface.

[0009] In a preferred embodiment, the following components are included in parts by weight: 50-80 parts of micron copper powder, 20-60 parts of nano copper powder, 6-8 parts of organic solvent, 0.5-1 part of thickener, and 1-2 parts of corrosion inhibitor.

[0010] In a specific embodiment, the organic coating agent in the nano copper powder coated with the organic coating agent is selected from at least one of methylimidazole, benzotriazole, 1,2-bis(N-phenyl-N-aminoethylimidazoline)ethane chloride, proline, malic acid, citric acid, stearic acid, oleylamine, stearylamine, and palmitic acid;

[0011] Preferably, the average particle size of the nano copper powder is 10-300 nm, preferably 50-150 nm.

[0012] In a specific embodiment, the corrosion inhibitor is selected from one or more of sodium borohydride, sodium cyanoborohydride, sodium triacetoxyborohydride, 2-methylpyridine borane, sebacic acid, adipic acid, and itaconic acid.

[0013] In a specific embodiment, the tap density of the micron copper powder is greater than 5 g / cm 3 , the average particle size is 1 μm-10 μm, preferably 3-5 μm;

[0014] Preferably, the micron copper powder is micro-etched with dilute hydrochloric acid to remove the oxide layer, and then cleaned with alcohol.

[0015] In a specific embodiment, the organic solvent is a mixed ether solvent, preferably any one or more selected from terpineol, propylene glycol methyl ether, diethylene glycol butyl ether, propylene glycol ethyl ether, benzyl glycidyl ether, and triethanolamine.

[0016] In a specific embodiment, the thickener is selected from any one or more of polyvinyl alcohol, linear acrylic acid, polyvinyl pyrrolidone, and ethyl cellulose.

[0017] On the other hand, the method for preparing the aforementioned high-density printed circuit board interconnection copper paste comprises the following steps:

[0018] S1, putting nano copper powder into an organic coating agent aqueous solution and stirring it thoroughly, and then washing and drying it after separation;

[0019] S2, mixing the organic solvent, corrosion inhibitor and thickener evenly, stirring until completely dissolved, to prepare a mixture a;

[0020] S3, putting the mixture a of step S2 and the nano copper powder and micron copper powder coated in step S1 into a planetary mixer in proportion and stirring them evenly, and dispersing them through a three-roll grinder to obtain interconnect copper slurry.

[0021] On the other hand, the aforementioned high-density printed circuit board interconnect copper paste or the pressureless sintering interconnect copper paste prepared by the aforementioned preparation method is used in high-power and high-density PCB inner layer interconnect packaging.

[0022] In a specific embodiment, the packaging process comprises the following steps:

[0023] 1) Cover the PCB with blind holes with PET film and drill holes at the blind holes with laser;

[0024] 2) Pour the aforementioned high-density printed circuit board interconnect copper paste onto the coated PCB board and fill it into the blind hole by scraping;

[0025] 3) Place the PCB board filled with interconnect paste into an oven for low-temperature surface drying;

[0026] 4) Carefully tear off the PET film covering the PCB board to avoid bringing the slurry out of the blind hole;

[0027] 5) Align another PCB board with the circuits to the blind hole of the PCB board that has been filled with interconnect paste, and perform high temperature and high pressure pressing after bonding;

[0028] Preferably, in step 1), the thickness of the PET film is 100-200 μm;

[0029] Preferably, in step 3), the low-temperature surface drying temperature is 60-90° C., and the surface drying time is at least 10 minutes.

[0030] Preferably, in step 5), the pressing temperature is 160-220° C. and the pressure is 2-5 MPa.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] When the metal particle size is reduced to the nanometer level, the specific surface energy increases with the reduction of particle size due to the increase in the proportion of surface atoms, and its melting point and sintering temperature will be greatly reduced. The high-density printed circuit board pressureless sintering interconnection copper paste of the present invention uses specially treated nano-scale metal powder. At a high temperature of more than 180 degrees at normal pressure, the highly active nano-metal powder undergoes pre-melting. At the same time, the corrosion inhibitor is introduced into the formula to effectively remove the oxide layer during the baking process, so as to achieve good bonding with the copper pad. At the same time, the low-temperature interconnection paste has an ultra-low organic content and high density because the organic components decompose or volatilize during the sintering process, retaining the good electrical and thermal conductivity of the bulk metal.

[0033] Compared with pressure sintering type interconnection paste, the pressureless sintering paste of the present invention does not require high pressure uniformity, and can achieve a bonding interconnection effect only by contact, thus achieving a higher pressing yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram of the interconnection structure of Example 1 of the present invention.

[0035] Figure 2 This is a schematic diagram of the interconnection structure of Example 5 of the present invention.

[0036] Figure 3 Schematic diagram of the interconnection structure of comparative example 1 of the present invention.

[0037] Figure 4 The figure is a schematic diagram of the hole chain structure of a PCB packaged in the present invention. DETAILED DESCRIPTION

[0038] In order to make the technical problem, technical solution and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to explain the present invention and is not used to limit the present invention.

[0039] Example 1

[0040] A high-density printed circuit board interconnect copper paste, comprising the following components by weight:

[0041]

[0042] The method for preparing the above-mentioned high-density printed circuit board interconnection copper paste comprises the following steps:

[0043] S1. Take 50g of nano copper powder with a D50 of 100nm, put it into 1kg of 10% proline aqueous solution and stir it for 60 minutes. After centrifugation, wash it with ethanol three times, centrifuge it again, and bake it in a 60-degree oven for 3 hours.

[0044] S2, mixing the above proportions of diethylene glycol butyl ether, 2-methylpyridine borane, and polyvinyl pyrrolidone uniformly, stirring until completely dissolved, to prepare a mixture a;

[0045] S3, putting the mixture a, the nano silver treated in step S1 and the micron copper powder with an average particle size of 5 μm into a planetary mixer in proportion and stirring them evenly, and dispersing them through a three-roll grinder to obtain a pressureless sintering interconnect copper paste.

[0046] In addition, the packaging process of the above-mentioned high-density printed circuit board interconnection copper paste includes the following steps:

[0047] 1) A 100 μm PET film is applied to the PCB with blind holes, and holes are drilled at the blind holes by laser.

[0048] 2) Pour the prepared interconnect paste onto the coated PCB board and fill it into the blind hole by scraping.

[0049] 3) Place the PCB board filled with interconnect paste in an oven for low-temperature surface drying for 10 minutes at a low-temperature surface drying temperature of 60°C.

[0050] 4) Carefully tear off the PET film covering the PCB board to avoid bringing the slurry out of the blind hole.

[0051] 5) Align another PCB board with circuits on it with the blind hole of the PCB board that has been filled with interconnect paste, and perform high temperature and high pressure pressing after lamination. The pressing temperature is 220℃ and the pressure is 3MPa to obtain Figure 1 The interconnect structure shown.

[0052] Example 2

[0053] Compared with Example 1, 2-methylpyridine borane was replaced by sodium borohydride, diethylene glycol butyl ether was replaced by a mixed solvent of triethanolamine and propylene glycol ethyl ether in a volume ratio of 2:3, and other conditions were exactly the same.

[0054] Example 3

[0055] Compared with Example 1, the nano copper is changed to 60 parts and the micron copper is changed to 30 parts; in step S1, the nano copper is coated with dimethylimidazole, and the other conditions are exactly the same.

[0056] Example 4

[0057] Compared with Example 2, in step S1, the nano-copper is coated with 1,2-di(N-phenyl-N-aminoethylimidazoline)ethane chloride, and the other conditions are exactly the same.

[0058] Example 5

[0059] Compared with Example 2, the nano copper coating agent in step S1 is changed to dimethyl imidazole, and the other conditions are exactly the same. The interconnection structure obtained by the final packaging process is as follows Figure 2 shown.

[0060] Comparative Example 1

[0061] Compared with Example 1, the nano copper does not undergo the coating treatment in step S1, and 2-methylpyridine borane is not added to the slurry, and other conditions are exactly the same. The interconnect structure obtained by the final packaging process is as follows Figure 3 shown.

[0062] Comparative Example 2

[0063] Compared with Example 1, commercially available copper-tin type interconnect copper paste PHP9000-5F-L (Shenzhen Bairou New Material Technology Co., Ltd.) was used to replace the pressureless sintering interconnect paste to plug the blind vias, and other conditions were exactly the same.

[0064] Examples 1 to 5 and Comparative Examples 1 to 2 were characterized, and the performance characterization steps included:

[0065] ① Thermal conductivity test: The interconnect slurry was pressed at 3MPa pressure and 220 degrees for one hour to prepare a module with a diameter of 12.5mm and a thickness of 2mm. The thermal conductivity was tested by laser flash method.

[0066] ②Hole chain resistance test: Use a micro resistance meter to test the resistance of the same hole chain on the pressed PCB board. The hole chain structure is as follows: Figure 4 shown.

[0067] ③Hot and cold shock reliability test: Place the pressed PCB board in -40℃ and 150℃ environment for hot and cold cycle test to test the change rate of hole chain resistance.

[0068] ④ Reflow test: According to the reflow temperature curve with the highest temperature of 280℃, the pressed PCB board is passed through the reflow oven for 5 times, and the resistance change rate is tested.

[0069] The specific test methods and evaluation criteria are shown in Table 1, and the test results are shown in Table 2.

[0070] Table 1

[0071]

[0072] Table 2

[0073]

[0074] It can be seen from Table 2 that compared with the comparative example, the organically coated nano copper powder in the embodiment of the present invention has higher reliability, and the resistance change rate of the hot and cold shock and reflow tests is less than 10%; while the hole chain resistance of the comparative example is 1-100Ω, and the resistance consistency is poor, which is mainly caused by the oxidation reaction of copper in the air atmosphere. Figure 1 , Figure 2 and Figure 3 The comparison can also be seen.

[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high-density printed circuit board interconnect copper paste, characterized in that: The invention comprises the following components in parts by weight: 30-90 parts of micron copper powder, 10-80 parts of nano copper powder, 4-10 parts of organic solvent, 0.01-2 parts of thickener and 0.5-3 parts of corrosion inhibitor, wherein the nano copper powder is nano copper powder coated with an organic coating agent.

2. The interconnect copper paste according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 50-80 parts of micron copper powder, 20-60 parts of nano copper powder, 6-8 parts of organic solvent, 0.5-1 part of thickener and 1-2 parts of corrosion inhibitor.

3. The interconnect copper paste according to claim 1 or 2, characterized in that: The organic coating agent in the nano copper powder coated with the organic coating agent is selected from at least one of methylimidazole, benzotriazole, 1,2-bis(N-phenyl-N-aminoethylimidazoline)ethane chloride, proline, malic acid, citric acid, stearic acid, oleylamine, stearylamine, and palmitic acid; Preferably, the average particle size of the nano copper powder is 10-300 nm, preferably 50-150 nm.

4. The interconnect copper paste according to claim 1 or 2, characterized in that: The corrosion inhibitor is selected from one or more of sodium borohydride, sodium cyanoborohydride, sodium triacetoxyborohydride, 2-methylpyridine borane, sebacic acid, adipic acid and itaconic acid.

5. The interconnect copper paste according to claim 1, characterized in that: The tap density of the micron copper powder is greater than 5g / cm 3 , the average particle size is 1 μm-10 μm, preferably 3-5 μm; Preferably, the micron copper powder is micro-etched with dilute hydrochloric acid to remove the oxide layer, and then cleaned with alcohol.

6. The interconnect copper paste according to claim 1, characterized in that: The organic solvent is a mixed ether solvent, preferably any one or more selected from terpineol, propylene glycol methyl ether, diethylene glycol butyl ether, propylene glycol ethyl ether, benzyl glycidyl ether, and triethanolamine.

7. The interconnect copper paste according to claim 1, characterized in that: The thickener is selected from any one or more of polyvinyl alcohol, linear acrylic acid, polyvinyl pyrrolidone and ethyl cellulose.

8. The method for preparing a high-density printed circuit board interconnection copper paste according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, putting nano copper powder into an organic coating agent aqueous solution and stirring it thoroughly, and then washing and drying it after separation; S2, mixing the organic solvent, corrosion inhibitor and thickener evenly, stirring until completely dissolved, to prepare a mixture a; S3, putting the mixture a of step S2 and the nano copper powder and micron copper powder coated in step S1 into a planetary mixer in proportion and stirring them evenly, and dispersing them through a three-roll grinder to obtain interconnect copper slurry.

9. Use of the high-density printed circuit board interconnection copper paste according to any one of claims 1 to 7 or the interconnection copper paste prepared by the preparation method according to claim 8 in high-density printed circuit board interconnection packaging.

10. The use according to claim 9, characterized in that: The interconnect packaging process includes the following steps: 1) Cover the PCB with blind holes with PET film and drill holes at the blind holes with laser; 2) pouring the high-density printed circuit board interconnection copper paste according to any one of claims 1 to 7 onto the coated PCB board and filling it into the blind hole by scraping; 3) Place the PCB board filled with interconnect paste into an oven for low-temperature surface drying; 4) Carefully tear off the PET film covering the PCB board to avoid bringing the slurry out of the blind hole; 5) Align another PCB board with the circuits to the blind hole of the PCB board that has been filled with interconnect paste, and perform high temperature and high pressure pressing after bonding; Preferably, in step 1), the thickness of the PET film is 100-200 μm; Preferably, in step 3), the low-temperature surface drying temperature is 60-90° C., and the surface drying time is at least 10 minutes. Preferably, in step 5), the pressing temperature is 160-220° C. and the pressure is 2-5 MPa.

Citation Information

Cited By

  • Circuit base material applying nano-copper and preparation method and application of circuit base material

    CN120748808A